2022
DOI: 10.3389/fcvm.2022.881141
|View full text |Cite
|
Sign up to set email alerts
|

Role of Cardiovascular Magnetic Resonance in Native Valvular Regurgitation: A Comprehensive Review of Protocols, Grading of Severity, and Prediction of Valve Surgery

Abstract: Valvular regurgitation is common in developed countries with an increasing prevalence due to the aging of the population and more accurate diagnostic imaging methods. Echocardiography is the gold standard method for the assessment of the severity of valvular heart regurgitation. Nonetheless, cardiovascular magnetic resonance (CMR) has emerged as an additional tool for assessing mainly the severity of aortic and mitral valve regurgitation in the setting of indeterminate findings by echocardiography. Moreover, C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 95 publications
0
20
0
1
Order By: Relevance
“…Maréchaux et al reported that a cut-off of 3D-RegFrac ≥ 40% accurately discriminates patients with 3+ or 4+ MR, with a grey zone of overlap between 1+ or 2+ vs. 3+ or 4+ patients reduced by 3D-TTE compared to 2D-TTE (130). Consistently, CMR studies emphasized the discriminative value of a CMR-RegFrac ≥ 40%, that is below the 50% threshold still retained in guidelines, and with prognostic implications (181). Independently from the imaging modality used (2D-TTE, 3D-TTE, or CMR), further multicenter prospective studies should be conducted to standardize the severity thresholds of RegFrac based on outcome predictions in patients with primary MR.…”
Section: Discrepancies Between Quantitative Mr Parameters and Outcome...mentioning
confidence: 88%
“…Maréchaux et al reported that a cut-off of 3D-RegFrac ≥ 40% accurately discriminates patients with 3+ or 4+ MR, with a grey zone of overlap between 1+ or 2+ vs. 3+ or 4+ patients reduced by 3D-TTE compared to 2D-TTE (130). Consistently, CMR studies emphasized the discriminative value of a CMR-RegFrac ≥ 40%, that is below the 50% threshold still retained in guidelines, and with prognostic implications (181). Independently from the imaging modality used (2D-TTE, 3D-TTE, or CMR), further multicenter prospective studies should be conducted to standardize the severity thresholds of RegFrac based on outcome predictions in patients with primary MR.…”
Section: Discrepancies Between Quantitative Mr Parameters and Outcome...mentioning
confidence: 88%
“…Over the past 20–25 years, cardiovascular magnetic resonance (CMR) has established itself as the gold standard for assessing left and right ventricular mass, volume, and function. Additionally, it has developed into a trustworthy and precise tool for calculating the volumetric quantification of the heart valves utilizing a number of methods that are independent of jet morphology 19–21 . When evaluating TR using an integrated strategy that considers both qualitative and quantitative parameters, echocardiography is the recommended and advised initial imaging technique.…”
Section: Discussionmentioning
confidence: 99%
“…The most recent recommendations suggest applying the same severity criteria in regurgitant fraction for TR as have been applied for mitral regurgitation (i.e., a regurgitant fraction of less than 15% for mild TR, more than 15% for severe TR, and between 16% and 25% for moderately severe TR) 19,21,22 . The ferromagnetic effects of metallic implants, claustrophobia, respiratory artifacts, arhythmia artifacts, claustrophobia, the lack of technology in all centers, and a shortage of imaging professionals to interpret images are some of the drawbacks of CMR 19–22 . Regurgitant fraction predictors, a crucial factor in TR grading in CMR, must be found using echocardiographically similar methods.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations